2019
DOI: 10.1111/xen.12517
|View full text |Cite
|
Sign up to set email alerts
|

The complex functioning of the complement system in xenotransplantation

Abstract: The role of complement in xenotransplantation is well-known, and is a topic that has been reviewed previously. However, our understanding of the immense complexity of its interaction with other constituents of the innate immune response and of the coagulation, adaptive immune, and inflammatory responses to a xenograft is steadily increasing. In addition, the complement system plays a function in metabolism and homeostasis. New reviews at intervals are therefore clearly warranted. The pathways of complement act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 200 publications
(314 reference statements)
0
34
0
Order By: Relevance
“…These advances introduced the possibility of genetic modification of the organ-source pig for xenotransplantation. Today, many pigs expressing hCPRs have been produced [reviewed in (112)]. Researches have also demonstrated that expression of hCRPs can inhibit complement-mediated graft injury and prolong xenograft survival time (113,114).…”
Section: Expression Of Human Complement Regulatory Proteinsmentioning
confidence: 99%
“…These advances introduced the possibility of genetic modification of the organ-source pig for xenotransplantation. Today, many pigs expressing hCPRs have been produced [reviewed in (112)]. Researches have also demonstrated that expression of hCRPs can inhibit complement-mediated graft injury and prolong xenograft survival time (113,114).…”
Section: Expression Of Human Complement Regulatory Proteinsmentioning
confidence: 99%
“…The role of complement in xenotransplantation is well-known and is a topic that has been reviewed recently. 61 62 Little research has been carried out on the relationship between extracellular histones and the complement system. Cobra venom factor has been administered as an inhibitor of complement activation in pig-to-non-human primate xenotransplantation studies.…”
Section: Complementmentioning
confidence: 99%
“…Because recipient antibody binding is a significant barrier to xenotransplantation, the complement system is a primary contributor to rejection. Zhou et al 1 Zhou et al 1 specifically bring our understanding of the three pathways of the complement system (classical, lectin, and alternative) up to date and provide a useful illustration of the molecular interactions of recognizers, receptors, and regulators within and between these three pathways. [14][15][16] However, it is clear that despite ongoing advancement in complement system research, the mechanisms of the lectin pathway remain incomplete.…”
Section: Molecul Ar Mechanis Ms In Xenotr Ans Pl Antationmentioning
confidence: 99%
“…In the previous issue of Xenotransplantation, Zhou et al provided an updated review of the complement system in xenograft rejection; Hundrieser et al discuss how porcine and human MHC‐II polymorphisms influence donor reactivity; Ladowski et al seek to eliminate all donor xenoantigens; Cooper et al review a 9 gene alteration of porcine donors for clinical xenotransplantation; Zhou et al present a strategy to monitor xenograft rejection with porcine cDNA biomarkers; Zafar et al provide further research into reducing porcine islet immunoreactivity; Li et al studied the cold storage of porcine hepatocyte spheroids; Iizuka et al deep dive into porcine C‐peptide pharmacokinetics; and, finally, Zheng et al, Zhao et al, and Yoon et al provide updates in corneal xenotransplantation.…”
Section: Introductionmentioning
confidence: 99%